FIRST RECORD OF MONILIGASTRID EARTHWORMS FROM A SELECTED REGION OF THE GANGETIC PLAIN OF BIHAR, INDIA - ROHIT SRIVASTAVA; MRIDULA KUMARI; MANOJ KUMAR; RAKESH RANJAN; MANORANJAN PRASAD SINHA (The Bioscan, 2023)
The paper deals with description of two species of Genus Drawida Michaelsen found in different locations of the Gangetic plain of Bihar. Though the genus is native yet only two species were found in this region during the collection. The two species dealt with are Drawida calebi Gates and Drawida willsi Michaelsen. The occurrence of these species in the Gangetic plain indicated the suitability of the edaphic profile of the region to the earthworm species. Both the species are endogeic in nature.